Research on the tribological properties of a textured lubricating wear-resistant coating modified by nano-SiC at high temperature. Issue 1 (9th February 2015) - Zhao, Yuncai; Yang, Fei; Guo, Yongming
Abstract : Purpose: – The purpose of this paper is to investigate the tribological properties of a textured lubricating wear-resistant coating modified by nano-SiC at a high temperature. Its aim is to explore the influence of a new composite method on the organisation and structure of sprayed coatings as well as the evolution rules governing their high-temperature tribological properties. Design/methodology/approach: – A KF301/WS2 lubricating, wear-resisting, coating was prepared on matrix material GCr15 by applying supersonic plasma spraying technology. On the basis of this sample, using nano-SiC particles as a filler, the KF301/WS2 nano-modified coating with its round, pit-type texture was prepared by laser re-melting technology and a surface texturing technique. Two kinds of coating micro-organisations and structures were examined by scanning electron microscopy, and the tribological properties of both the modified and conventional coatings were studied at a high temperature. Findings: – Results showed that nano-particles could effectively improve the coating micro-structure, and make the structure denser and more uniform, thus significantly increasing the wear resistance of the coating. When the friction and wear processes were stable, the friction coefficient decreased by 13 per cent, while the wear loss decreased by 45.9 per cent. Originality/value: – This research concentrating on the study of the process and performance of coatings doped with nano-particles by laser re-melting incorporating simultaneous surface texturing, and studies of their high-temperature tribological properties. That is because applying nano-particle modification technology to the development of wear-resistant coatings, and by applying the nano-particles to such coatings by thermal spraying technology, they can achieve a modification of the coating which makes the structure denser and more uniform.